Malay dilemma on tadabbur al- Qur’an and translation of Hadith: a reflection - Mohd Marzuki, Zunaidah (2020)
The study of the Quran in the field of Tilawah (recitation), Tarannum (melodious recitation), and Tahfiz (memorization) has been enjoying a surge of attention of late, in Malay society that can be indicated by the increasing of various learning platforms intended for general learners. Least attention has been given to the study of Tafsir (commentary), Translation and Tadabbur (contemplation/reflection) of the Quran. However, among the three above-mentioned, Tadabbur has gained a foothold and become current trend amongst Malays especially for the purpose of bibliotherapy and self-motivation, other than reflective lesson (Ibrah) from the historical narratives of the Quran. Some people opine to such an extent that anyone could do Tadabbur for the purpose of searching answers to one’s problems which precisely known as “Tawassul bil-Qur’an” with the understanding that the Holy Quran is a guidance and mercy for all people. The “Tawassul bil-Qur’an” through “Garpu Tala” technique for example, nowadays, has gained popularity amongst Malays and its “random technique” has been subjected to criticism by many that it might be derived from Syiah’s technique of “Istikharah bil-Qur’an”. Therefore, the critics call society to have proper ethics in dealing with the Qur’an and suggest that Tadabbur of the Quran should not bypass the knowledge of Sciences of Qur’an and its Tafsir. Hence, the dilemma arises between application of Tadabbur and its right before making Tafsir in understanding and practicing the message of the Qur’an. Another religious dilemma in Malay folk is about the rarity of the translation of hadith books in Malay language. The translation project on Six Canonical Books of Hadith has been executing from time to time to fill the gap by individual and organization scholarship. However, many issues arise about the project such as the quality and the validity of the translation, the translators background and the consideration of bilingualism and biculturalism in translation. Keenly aware of these dilemmas, the task of the Tadabbur of the Quran and the Translation of Hadith should be taken carefully by scholars of its specialization and students should be properly developed to produce such a profound expertise in various Islamic fields and skills to serve the ummah in understanding the messages of the sacred texts and act upon them according to the Messenger`s guidance.